Disc Degeneration in Direct Injury or Instability Models Share Common Metabolic Pathways - Matthew Goodwin (Journal of Spine Practice)
Introduction: Disc degeneration is the central component involved in numerous common spinal pathologies. Degenerative disc disease affects millions of people every year, yet the mechanisms driving degeneration remain poorly understood. Previous work to date has shown that high levels of intracellular lactate seem to be involved in driving this pathology once thought to be purely mechanical. Here, we present a series of studies utilizing mouse models of mechanical injuring or loading of the intervertebral disc (IVD), with a goal of better defining the role of lactate and lactate transport in degenerative disc disease.